2014
DOI: 10.1371/journal.pone.0105250
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacogenetics-Based Warfarin Maintenance Dosing Algorithm from Northern Chinese Patients

Abstract: Inconsistent associations with warfarin dose were observed in genetic variants except VKORC1 haplotype and CYP2C9*3 in Chinese people, and few studies on warfarin dose algorithm was performed in a large Chinese Han population lived in Northern China. Of 787 consenting patients with heart-valve replacements who were receiving long-term warfarin maintenance therapy, 20 related Single nucleotide polymorphisms were genotyped. Only VKORC1 and CYP2C9 SNPs were observed to be significantly associated with warfarin do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
(70 reference statements)
0
28
0
Order By: Relevance
“…Although these algorithms can be used in clinical practice to predict the optimal warfarin dose before treatment initiation, their effectiveness has not completely demonstrated in clinical practice [31,32]. Moreover, human genetic variation could alter the accuracy of these algorithms when used in populations with genomic backgrounds different from those populations used for algorithm development and validation [16,17]. The Turkish population is a good example of a human group with peculiar genetic features that may affect the accuracy of the international warfarin algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these algorithms can be used in clinical practice to predict the optimal warfarin dose before treatment initiation, their effectiveness has not completely demonstrated in clinical practice [31,32]. Moreover, human genetic variation could alter the accuracy of these algorithms when used in populations with genomic backgrounds different from those populations used for algorithm development and validation [16,17]. The Turkish population is a good example of a human group with peculiar genetic features that may affect the accuracy of the international warfarin algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…These large efforts could provide reliable indications that could help clinicians define the warfarin dose on the basis of patient characteristics. However, human genetic diversity can significantly affect the reliability of these warfarin pharmacogenetic algorithms [16,17], as has been demonstrated in other pharmacogenomics contexts [18][19][20]. In particular, some human populations with peculiar genetic features, such as the Turkish population, have not been included in these large multiethnic investigations, and no information is available about the effectiveness of these warfarin pharmacogenetic algorithms in these human groups.…”
Section: Introductionmentioning
confidence: 99%
“…Several genome-wide association studies indicated that there seemed to be no other common SNPs with great effects on warfarin maintenance dose outside of CYP2C9, VKORC1 and CYP4F2 [23][24][25]. Recent association studies with the Chinese population also confirmed this observation [12,[26][27][28]. In this study, genetic polymorphisms of these three candidate genes were systematically investigated in the warfarin-sensitive patient.…”
Section: Discussionmentioning
confidence: 61%
“…Recently, four research groups reported their retrospective study results using large-scale numbers (297-845) of Chinese patients with a stable maintenance dose of warfarin [12,[26][27]30]. According to their results, the warfarin maintenance dose of Chinese individuals with the genotype CYP2C9*1/*1 is usually 3.0-3.69 mg/day, while patients carrying the heterozygous genotype *1/*3 required 2.13-2.74 mg/day, which is only about a 35% lower dose requirement than those with wildtype.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the clinicopathological findings were associated with genetic factors, written informed consent was obtained from the patient to perform genetic testing. Five genetic variations associated with a required increase in the warfarin dose, namely CYP4F2, γ glutamyl carboxylase, protease, serine 53 and NAD(P)H quinone dehydrogenase 1 were identified, besides the common mutation in VKORC1 (rs7294) in Chinese individuals (Table II) (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%